The Effect of Consumer-Based Brand Equity and Satisfaction on Loyalty: An Empirical Study - Muhammad Andreaginola Pratama; Rizki Pratama Saleh Siregar; Sabrina Oktaria Sihombing (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2019)
Abstract: Economic growth in Indonesia encourages the growth of many industries. Specifically, the food and beverage industry has grown significantly in Indonesian economics. Coffee shops with foreign or local brands are growing and competing for having customer loyalty. Many research has been conducted to examine customer loyalty in a particular coffee shop. However, little research has been focused on comparing both local and foreign brand names of the coffee shop. The comparative study is needed to understand whether foreign or local brand names matter in predicting both customer satisfaction and loyalty. This research uses a quantitative paradigm using descriptive research type. The object of research is Starbucks (foreign brand) and Djournal Coffee (local brand). Data were collected through questionnaires distributed by applying judgemental sampling. Data analysis was conducted by using structural equation model (SEM). In this study, there are two unsupported hypotheses namely (1) the relationship between the ideal self-congruence and customer satisfaction, and (2) the relationship between brand identification and customer satisfaction. The study also provides theoretical contributions, managerial implications and suggestions for further research. Keywords: brand equity, customer satisfaction, brand loyalty, SEMPengaruh Ekuitas Merek Berbasis Konsumen dan Kepuasan terhadap Loyalitas: Sebuah Studi Empiris Abstrak: Pertumbuhan ekonomi di Indonesia mendorong pertumbuhan banyak industri. Secara khusus, industri makanan dan minuman telah tumbuh secara signifikan dalam ekonomi Indonesia. Kedai kopi dengan merek asing atau lokal tumbuh dan bersaing untuk memiliki loyalitas pelanggan. Banyak penelitian telah dilakukan untuk menguji loyalitas pelanggan di coffee shop tertentu. Namun, sedikit penelitian yang difokuskan untuk membandingkan nama merek lokal dan asing dari coffee shop. Studi perbandingan diperlukan untuk memahami apakah nama merek asing atau lokal penting dalam memprediksi kepuasan dan loyalitas pelanggan. Penelitian ini menggunakan paradigma kuantitatif dengan menggunakan tipe penelitian deskriptif. Objek penelitian adalah Starbucks (merek asing) dan Djournal Coffee (merek lokal). Data dikumpulkan melalui kuesioner yang didistribusikan dengan menggunakan judgemental sampling. Analisis data dilakukan dengan menggunakan pemodelan persamaan struktural (SEM). Dalam penelitian ini ada dua hipotesis yang tidak didukung yaitu (1) hubungan antara kongruensi diri yang ideal dan kepuasan pelanggan dan (2) hubungan antara identifikasi merek dan kepuasan pelanggan. Studi ini juga memberikan kontribusi teoritis, implikasi manajerial dan saran untuk penelitian lebih lanjut. Kata kunci: ekuitas merek, kepuasan konsumen, loyalitas merek, SEM